Cognitive abilities, insurance decisions, and labor supply behavior: evidence from rural China - Yang, Ziyue (Frontiers in Public Health, 2024)
How cognitive abilities affect financial and economic decision is an important issue that has attracted the attention of economics. This paper uses the China Family Panel Studies (CFPS) 2010, 2014, and 2018 survey data to empirically test the impact of cognitive skills on the insurance participation decisions in rural China. The results show that higher word ability is correlated to higher social health insurance participation and both word and math ability leads to higher social pension participation. Mechanism analysis reveals that individuals with higher cognitive skills are more likely to be affected by peers in insurance decision, and higher cognitive skills increase personal income that enables them to enroll in the social insurance. Further investigation of labor supply behavior suggests that while cognitive skills positively affect non-agricultural labor participation, cognitive skills amplify the negative effect of social security on labor supply.